Breeding success of a colony of Boat-billed Herons Cochlearius cochlearius (Ciconiiformes: Ardeidae) in pasturelands of Costa Rica - Gómez, Jaime (2006)
The breeding success of a double-brooding colony of Boat-billed Herons Cochlearius cochlearius was studied in pasturelands of Costa Rica. Mean clutch size in the first clutches (2.9 eggs/nest) was higher than in second and repeat clutches (2.3 eggs/nest). Breeding success was similar in the first attempt and second attempts (20.7 % and 21.7 %, respectively). In both attempts earlier nests enjoyed a higher breeding success. Starvation of the youngest chicks within the nest and destruction of nests by bad weather conditions were the main factors related to nestling death. No effects of human activity on the reproduction of the breeding colony were observed.